Usefulness of immunohistochemistry in differential diagnosis of epithelial renal and adrenal gland tumors - Kubiak, Robert; Kopczyński, Janusz; Pasz-Walczak, Grażyna; Jesionek-Kupnicka, Dorota; Kordek, Radzisław (Contemporary Oncology/Współczesna Onkologia, 2004)
The diagnosis of epithelial renal tumors is usually not difficult, except for some rare cases, especially of metastatic tumors. The use of immunohistochemistry with a targeted panel of antibodies can help us to make the right diagnosis. According to recently published data, we can assent that a combination of five antibodies, CK7, CK20, 34betaE12, CD10 and Vimentin is sufficient in differential diagnosis of renal cell tumors. We encounter many more diagnostic problems with the diagnosis of the adrenal gland tumors. The assessing of biologic behavior of these lesions can be also quite difficult. Although, the immunohistochemistry can distinguish the cortical tumors from the medullary ones and some other epithelial tumors, but in the prognostic field the IHC is insignificant and the diagnosis is still based on the morphological criteria. In summary, the analysis of the immunophenotype, using antibodies like Cytokeratin, D-11 renal marker, Calretinin, Inhibin, bcl-2 and Synaptophysin can be useful in differentiation between tumors: medullary, cortical and other epithelial ones. Up to now, there is no antibody, which can help us to evaluate the biological behavior of the adrenal gland tumors.